2017
DOI: 10.1007/s13402-017-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucosidase II beta subunit (GluIIβ) plays a role in autophagy and apoptosis regulation in lung carcinoma cells in a p53-dependent manner

Abstract: Our data indicate that GluIIβ inhibition results in autophagy and apoptosis in lung carcinoma-derived cells, supporting the hypothesis that this enzyme may play a role in blocking these two tumor suppressive processes. Since blocking autophagy by lysosomal inhibitors enhanced the apoptosis-inducing effect of bromoconduritol, independent of p53 status, their combined use may hold promise for the treatment of cancer, particularly lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…mTOR 33 , thus RTKs inhibition can have a direct impact over autophagy regulation. Accordingly, suppression of GluIIβ activity either by a selective inhibitor or siRNA technology has been repeatedly reported to cause an induction of autophagy 4,5 , which may additionally be support by our finding that knock-out of GluIIβ down-regulated multiple RTK signaling activities leading to autophagy. Our previous study demonstrated that suppression of GluIIβ not only induced autophagy but also induced apoptosis, and the inhibition of autophagy could enhance the apoptosis inducing effect of GluIIβ suppression.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…mTOR 33 , thus RTKs inhibition can have a direct impact over autophagy regulation. Accordingly, suppression of GluIIβ activity either by a selective inhibitor or siRNA technology has been repeatedly reported to cause an induction of autophagy 4,5 , which may additionally be support by our finding that knock-out of GluIIβ down-regulated multiple RTK signaling activities leading to autophagy. Our previous study demonstrated that suppression of GluIIβ not only induced autophagy but also induced apoptosis, and the inhibition of autophagy could enhance the apoptosis inducing effect of GluIIβ suppression.…”
Section: Discussionsupporting
confidence: 86%
“…We previously reported detecting increased expression of GlluIIß in a high proportion of lung carcinoma tissues 3 , and suppression of GlluIIß triggered cells to undergo autophagy and/or apoptosis 46 . In this study we have demonstrated that knockout of GlluIIß significantly decreased viability, migration, anchorage-independent growth and RTKs signaling activities of lung cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations